English Pragmatic Competence of Col Language Speakers in Using Directive Act at Lubuklinggau - Afifah Wahyuningsih; Sastika Seli; Dewi Syafitri (EDULIA: English Education, Linguistic and Art Journal, 2023)
This research aimed to explain the English Pragmatic Competence of Col language speakers in using directive act and to find out the extent to which Col language pragmatic competence influence the production of English pragmatic competence in directive act. The method used descriptive qualitative. The research subjects were 20 students who studied English consisting of students, collage students and graduates at Lubuklinggau. The data were collected by using questionnaire and pragmatic competence test. After that, the data were analyzed with description. The result of this research is that the pragmatic competence of Col language using directive acts is more understandable because respondents understand the use of language in the right situation may be different. The tests that have been carried out show that many of the respondents' answers are appropriate. They use English only in educational domains such as schools, colleges and courses. Therefore, the frequency of use of English is limited and other languages are used more frequently. In almost all expressions there is no significant negative transfer from L1 and L2 production to English, as all percentages below 50% except 57,5% command expressions have little influence on English production. These errors were found in the use of expressions in several formal situations, but they were not significant because not many pragmatic errors were found. In conclusion is that Col people understand how to use appropriate expressions in different situations, namely formal and informal situations, even though only the expressions of command have little influence. Keywords: Col Language Speakers, Directive Act, Pragmatic Competence